A Gneralized Frequency-Temperature Viscoelastic Model - R.A.S. Moreira; J.D. Corte-Real; J. Dias Rodrigues (Shock and Vibration)
The design of passive damping treatments using viscoelastic materials requires both an accurate numerical analysis approach, usually making use of the finite element method, and a realistic means of material description. While the former has been widely studied and several and valuable approaches have become available during the last years, the latter is still an issue requiring additional efforts. The experimental characterization, the data modeling and finally the constitutive models able to be directly used along analytic and numerical analysis, are still important research areas. Several viscoelastic models, able to be directly applied into a finite element analysis either in a time or in a frequency domain analysis, are available and have been widely used during the last years in most of the published work. Despite the general description and straightforward use that such modeling approaches may provide, temperature effect is usually disregarded and isothermal analysis are usually performed. Moreover, this temperature effect is naturally not directly considered as an input parameter for most of the viscoelastic material models and isothermal conditions are also considered in the experimental characterization data analysis. This work presents an extended viscoelastic model, based on well known isothermal models, where the temperature-frequency superposition effect is directly considered. The extended model is applied to the analysis of the experimental data using a data fitting procedure to identify a set of global parameters able to represent the effect of the frequency and the temperature.